Order Statistics in Goodness-of-Fit Testing - Glen, Andrew G.; Barr, Donald R.; Leemis, Lawrence M. (Computational Probability Applications, 2017)
A new method is presented for using order statistics to judge the fit of a distribution to data. A test statistic based on quantiles of order statistics compares favorably with the Kolmogorov–Smirnov and Anderson–Darling test statistics. The performance of the new goodness-of-fit test statistic is examined with simulation experiments. For certain hypothesis tests, the test statistic is more powerful than the Kolmogorov–Smirnov and Anderson–Darling test statistics. The new test statistic is calculated using a computer algebra system because of the need to compute exact distributions of order statistics.